Autism in Brazil: a systematic review of family challenges and coping strategies - Paulyane T.M. Gomes; Leonardo H.L. Lima; Mayza K.G. Bueno; Liubiana A. Araújo; Nathan M. Souza (Elsevier, 2015)
OBJECTIVE: To describe the challenges faced by families caring for children with autism spectrum disorder (ASD) in Brazil and the coping strategies employed. SOURCES: Systematic review of articles published until September of 2013, without language restrictions, using quality appraisal (AMSTAR and CASP/Oxford instruments). SUMMARY OF THE FINDINGS: The literature shows parental emotional overload as one of the main challenges faced by families, especially mothers. The main stressors were diagnostic postponement, difficulty dealing with the diagnosis and associated symptoms, and poor access to health services and social support. The predominant coping strategies found included information exchange between affected families and integrated healthcare network for patient and family support. CONCLUSION: ASD exerts strong influence on family dynamics, resulting in caregiver overload, especially in mothers. The Brazilian Unified Health System needs to provide comprehensive, continuous, and coordinated care to strengthen the patient-family dyad and promote the full development and societal inclusion of children with ASD.